Metal-Organic Framework MOF-76(Nd): Synthesis, Characterization, and Study of Hydrogen Storage and Humidity Sensing - Garg, Akash; Almáši, Miroslav; Rattan Paul, Devina; Poonia, Ekta; Luthra, J. R.; Sharma, Anshu (Frontiers in Energy Research, 2021)
The nanoporous metal-organic framework (MOF), MOF-76(Nd) [neodymium (III) benzene-1,3,5-tricarboxylate], has been synthesized, characterized, and tested for hydrogen storage and humidity sensing applications. These synthesized MOFs were characterized using scanning and transmission electron microscopy techniques. Thermal analysis revealed that, after the dehydration process, the compound showed high thermal stability up to 500°C. Hydrogen adsorption/desorption measurements of MOF-76(Nd) were performed at 77K and 20 bar and the material was further used for the humidity measurement at room temperature.